Optimization of E-Service Quality and Market Orientation on Customer Satisfaction of Fashion Products in E-Commerce - Amelia Putri Utami; Suyono Suyono (LPPM Institut Bisnis dan Informatika Kesatuan, 2024)
This study aims to explore the optimization of e-service quality and market orientation in fashion products within e-commerce, focusing on their impact on customer satisfaction. The research contributes to understanding the interplay between these variables in enhancing consumer experiences, particularly in the competitive digital marketplace. A quantitative approach was adopted, involving the distribution of structured questionnaires to 100 respondents, all students of the Faculty of Economics and Business, Trunojoyo University. The independent variables, e-service quality (X1) and market orientation (X2), were analyzed against the dependent variable, customer satisfaction (Y), using linear regression. Findings reveal that both e-service quality and market orientation significantly and positively influence customer satisfaction. Improved e-service quality fosters trust and loyalty by addressing consumer expectations, while market orientation ensures businesses remain attuned to customer needs and market trends. Together, these factors account for 65.9% of variations in customer satisfaction, underscoring their critical role in the success of e-commerce strategies. The study highlights the need for ongoing innovation in service quality and a customer-centric approach in market orientation to maintain a competitive edge. Future research could expand on this work by exploring additional variables or focusing on different e-commerce sectors. These insights provide valuable implications for businesses seeking to enhance customer satisfaction and sustain growth in the rapidly evolving e-commerce landscape.